Application of the Six Sigma methodology in the evaluation of the results in Cell Blood Count EQAS Program (PNAEQ) - Ovelheiro, Ana (2019)
The haemogram is one of the most frequently requested laboratory tests, in hospital and ambulatory It is important in the evaluation of anaemia, polycythaemia, leukaemia, infection, inflammation, among others Therefore, given the importance of the haemogram in the clinical context, an evaluation was performed on the results of the clinical laboratories participating in PNAEQ’s EQA Cell Blood program.